Recalculating national occurrence of microplastics in China’s freshwater - Dongyu Xu; Bo Gao (Cell Reports Sustainability)
Summary: Microplastics are ubiquitous in freshwater; however, non-harmonization of field observations for microplastics impedes their comparability, leading to an unclear national status. Here, we developed a “size-abundance” correction method based on field observation, which could align microplastic abundances into the same size range and be well validated. After reshaping the reported data (n = 1,331), national patterns and ecological risk of microplastics in China’s freshwater are explored. The average microplastic abundance in China’s freshwater is 4,785 ± 7,130 particles/m3, indicating that the reported data are considerably underestimated. The annual variation of microplastic abundances exhibits a stable decrease from 2016 to 2022. Although 79.7% of the sampling sites show microplastic accumulation, 83.9% of the locations are associated with a low ecological risk. Unexpectedly, the undeveloped regions in northwestern China face a high ecological risk. Our study contributes to the rescaling of microplastic patterns in freshwater nationally in China and can be applied globally. Science for society: Non-harmonization of field observations for microplastics has constrained the understanding of their occurrence characteristics in freshwater ecosystems, especially for China. In this paper, we developed a mathematical method to align the abundance of microplastics into the same size range. This “size-abundance” correction method not only improves the comparability among previously reported data for microplastic abundances, but it also reshapes the national patterns and ecological risks of microplastic in China’s freshwater. After aligning the reported data, the average microplastic abundances in surface water exhibited a stable decrease from 2016 to 2022 nationwide. Most of the locations in China’s freshwater faced a low ecological risk after correction calculation. Our study is a good attempt to rescale microplastic patterns in freshwater nationally and can be applied globally.